Respon Pemberian Tepung Daun Kelor (Moringa oleifera) pada Pakan Ayam Petelur terhadap Penampilan Produksi dan Kualitas Telur - Edi Wahyu Satria; Osfar Sjofjan; Irfan Hadji Djunaidi (Faculty of Animal Science, Universitas Gadjah Mada, 2016)
The purpose of this study was to determine the effect of Moringa leaf meal (Moringa oleifera) in feed on production performance and egg quality of laying hens. The materials used 120 laying hens of Isa Brown breed in 38 to 42 weeks age. The method used an experimental trial by Moringa oleifera addition in the basal feed. The experiment were devided into four groups i.e. without Moringa oleifera as control (P0), with Moringa oleifera 0.5% (P1), 1% (P2), 1.5% (P3) and 2% (P4). Variables observed were the appearance of egg production and quality. The data was analyzed by Completely Randomized one way design. The mean differences were calculated by the Duncan Multiple Range Test. The results showed that administration of Moringa leaf powder can increase the production and quality of eggs in laying hens. Addition of 2% Moringa leaf powder in the feed gives the best effect on the appearance and quality of production and egg. This research suggested the addition of 2% Moringa leaf powder was recommended in order to obtain the finest appearance and quality of production.